The impact of diet and gut microbiota on development, treatment, and prognosis in prostate cancer - Liu, Guanmo; Yang, Fan; Song, Wei; Hou, Rui (Frontiers in Nutrition, 2025)
Prostate cancer (PCa) progression is driven by a complex interplay of factors, including genetics, lifestyle, and environmental influences. Diet and gut microbiota have emerged as pivotal cancer development and treatment response modulators. This review delves into the intricate relationship between dietary modifications and gut microbiota, and their combined impact on PCa progression. Diets abundant in plant-based foods, fiber, and prebiotics promote beneficial gut microbiota profiles that support anti-inflammatory and anti-carcinogenic processes. In contrast, the Western dietary pattern, characterized by high levels of saturated fats and processed foods, may lead to dysbiosis, fostering pro-inflammatory conditions and the production of metabolites that enhance tumorigenesis. The gut microbiota influences the behavior of PCa through immune modulation, metabolic by-products, and interactions with systemic therapies. Emerging evidence, primarily derived from preclinical models or studies in non-PCa contexts, suggests that diet and gut microbiota may influence the development and progression of PCa. However, further PCa-specific clinical research is needed to validate these associations. Future research should prioritize the development of precise dietary recommendations and microbiota-targeted therapies that can be seamlessly incorporated into clinical practice for more personalized and effective cancer care.